Copper-Catalyzed Aerobic Oxidative Alkynylation of 3,4-Dihydroquinoxalin-2-ones - Rostoll-Berenguer, Jaume; Blay, Gonzalo; Pedro, José R.; Vila, Carlos (Synthesis, 2020)
Herein, we described a ligand-free copper-catalyzed aerobic oxidative functionalization of 3,4-dihydroquinoxalin-2(1H)-ones with terminal alkynes using visible-light and oxygen as terminal oxidant to give 3-ethynyl-3,4-dihydroquinoxalin-2(1H)-one, cyclic propargylic amines, in moderate to good yields. Moreover, we demonstrate the versatility of the 3-ethynyl-3,4-dihydroquinoxalin-2(1H)-ones obtained by preparing several 3,4-dihydroquinoxalin-2-one derivatives.
Keywords: dihydroquinoxalinones; alkynes; copper; cross-dehydrogenative coupling; oxidation; nitrogen heterocycles